The transhumanist reader: classical and contemporary essays on the science, technology, and philosophy of the human future. - More, Max; Vita-More, Natasha (WILEY, 2013)
The first authoritative and comprehensive survey of the origins and current state of transhumanist thinking The rapid pace of emerging technologies is playing an increasingly important role in overcoming fundamental human limitations. Featuring core writings by seminal thinkers in the speculative possibilities of the posthuman condition, essays address key philosophical arguments for and against human enhancement, explore the inevitability of life extension, and consider possible solutions to the growing issues of social and ethical implications and concerns. Edited by the internationally acclaimed founders of the philosophy and social movement of transhumanism, The Transhumanist Reader is an indispensable guide to our current state of knowledge of the quest to expand the frontiers of human nature.